Temporary immersion system, medium consistency and rooting in the micropropagation of the bamboo Dendrocalamus asper (Schult.) Backer - Carolina K. Marchetti; Thiago S. Ornellas; Ricardo Bittencourt; Luis E. Oviedo Zumaque; Marcelo F. Pompelli; Miguel Pedro Guerra (South African Journal of Botany, 2026)

Integrated cryopreservation and micropropagation for Chusquea mimosa: a strategy for ex situ conservation of a rare Brazilian bamboo - Carolina Marchetti; Julia Zappelini; Thiago Ornellas; Marcelo F. Pompelli; Alfredo Jarma-Orozco; Miguel Pedro Guerra (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Corrigendum to “Temporary immersion system, medium consistency and rooting in the micropropagation of the bamboo Dendrocalamus asper (Schult.) Backer” [South African Journal of Botany 196: 169-178, 2026] - Carolina K. Marchetti; Thiago S. Ornellas; Ricardo Bittencourt; Luis E. Oviedo Zumaque; Marcelo F. Pompelli; Miguel P. Guerra (South African Journal of Botany, 2026)

An evaluation of the utility of blood concentration of somatic mutagens to inform germ cell mutagenic hazard - Roger Godschalk; Bente Brauwers; Connie L. Chen; Raffaella Corvi; Kerry L. Dearfield; George R. Douglas; Naveed Honarvar; David Kirkland; Frank Le Curieux; Ann-Karin Olsen; Stefan Pfuhler; Leon F. Stankowski; et al. (Regulatory Toxicology and Pharmacology, 2026)

Comparison of submerged and air liquid interface exposure: limitations and differences in the toxicological effects evaluated in bronchial epithelial cells - Y. Allouche; S. Marchetti; R. Bengalli; G. Motta; L. Pagliarulo; F. Cazier; S. Achard; M. Fadel; P. Mantecca; D. Courcot; F. Ledoux; A. Verdin; et al. (Environmental Research, 2025)

Inhalation of nanoplastics in the mouse model: Tissue bio-distribution and effects on the olfactory system - G. Prosperi; N. Marchetti; A. D'Elia; R. Massari; M. Giusto; A. Pietrodangelo; T. Rossi; A. Nucara; F. Scavizzi; G. Strimpakos; S. Marinelli; S. Mandillo; et al. (Science of The Total Environment, 2025)

Alkali, thermal, or thermo-alkali pre-treatment to improve the anaerobic digestion of poly(lactic acid)? - C. Vasmara; G. Cazaudehore; E. Ceotto; R. Marchetti; C. Sambusiti; F. Monlau (Water Research, 2024)

A case of feline gastrointestinal eosinophilic sclerosing fibroplasia extending to the liver - M. Orlandi; F. Abramo; V. Habermass; E. Gori; V. Marchetti (Journal of Comparative Pathology, 2024)

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Origin and early evolution of vertebrate burrowing behaviour - Lorenzo Marchetti; Mark J. MacDougall; Michael Buchwitz; Aurore Canoville; Max Herde; Christian F. Kammerer; Jörg Fröbisch (Earth-Science Reviews, 2024)

Floating rooted hydrophytes and flow and sediment dynamics: Field study in secondary channels of the Paraná River - Z.Y. Marchetti; F. Latosinski; A. Carrasco Milian; C.G. Ramonell (CATENA, 2024)

Investigation of HER2 gene amplification and protein expression in canine primary pulmonary carcinoma - B. Brunetti; R. Marchetti; F. Millanta; G. Tura; L.V. Muscatello; E. Di Oto; E.L. Laddaga; A. De Leo; G. Tallini; B. Bacci (Journal of Comparative Pathology, 2023)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Protistan Communities Within the Galápagos Archipelago With an Emphasis on Micrograzers - Se Hyeon Jang; Prisca Lim; Olivia Torano; Erika F. Neave; Harvey Seim; Adrian Marchetti (Frontiers in Marine Science, 2022)
The Galápagos Archipelago is a globally significant biodiversity hotspot. However, compared to the relatively well-known megafauna, the distribution and ecological significance of marine protists in this system are poorly understood. To gain an understanding of the protistan assemblages across trophic modes, an intensive oceanographic survey was conducted in the Galápagos Marine Reserve (GMR) in October of 2018. The Equatorial Undercurrent (EUC)-influenced region had higher chlorophyll- a (Chl- a ) concentrations than those of the eastern regions of the archipelago, along with higher abundances of protistan grazers. Specifically, proportions of autotrophic and potentially mixotrophic dinoflagellates were higher in the EUC, whereas in the eastern regions, heterotrophic dinoflagellates and chlorophytes dominated. Taxonomic composition and biochemical indicators suggested proportions of micrograzers and their associated heterotrophic biomass was higher in the oligotrophic, low Chl- a regions in the east. We also report observations from a dinoflagellate bloom in the western archipelago, which was heavily influenced by upwelling of the EUC. The red tide-forming dinoflagellate Scrippsiella lachrymosa was highly detected through light microscopy and DNA amplicon sequencing. In addition, the heterotrophic dinoflagellate Polykrikos kofoidii was detected and, based on cell densities observed in this study and grazing rates obtained from the literature, estimated to potentially graze up to 62% of S. lachrymosa bloom population. Our findings thus provide new insights into the composition of micrograzers and their potential roles in structuring protistan communities in the Galápagos Archipelago.

Protistan plankton communities in the Galápagos Archipelago respond to changes in deep water masses resulting from the 2015/16 El Niño - Erika F. Neave; Harvey Seim; Scott M. Gifford; Olivia Torano; Zackary I. Johnson; Diego Páez‐Rosas; Adrian Marchetti (Environmental Microbiology, 2022)
Summary The Galápagos Archipelago lies within the Eastern Equatorial Pacific Ocean at the convergence of major ocean currents that are subject to changes in circulation. The nutrient‐rich Equatorial Undercurrent upwells from the west onto the Galápagos platform, stimulating primary production, but this source of deep water weakens during El Niño events. Based on measurements from repeat cruises, the 2015/16 El Niño was associated with declines in phytoplankton biomass at most sites throughout the archipelago and reduced utilization of nitrate, particularly in large‐sized phytoplankton in the western region. Protistan assemblages were identified by sequencing the V4 region of the 18S rRNA gene. Dinoflagellates, chlorophytes and diatoms dominated most sites. Shifts in dinoflagellate communities were most apparent between the years; parasitic dinoflagellates, Syndiniales , were highly detected during the El Niño (2015) while the dinoflagellate genus, Gyrodinium , increased at many sites during the neutral period (2016). Variations in protistan communities were most strongly correlated with changes in subthermocline water density. These findings indicate that marine protistan communities in this region are regimented by deep water mass sources and thus could be profoundly affected by altered ocean circulation.

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients - L. Paglicci; V. Borgo; N. Lanzarone; M. Fabbiani; C. Cassol; MG. Cusi; M. Valassina; S. Scolletta; E. Bargagli; L. Marchetti; P. Paladini; L. Luzzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart diseases were independently associated to a higher risk of overall bacterial colonization. Peptic diseases conferred a higher risk of multi-drug resistant (MDR) colonization, while longer duration of aerosol prophylaxis was associated with a lower risk. Overall, 35% of lung recipients developed bacterial pneumonia. COPD (when compared to idiopathic pulmonary fibrosis, IPF) and higher BMI were associated to a lower risk of bacterial infection. A higher risk of MDR infection was observed in IPF and in patients with pre-transplant colonization and infections. The risk of post-LT respiratory infections could be stratified by considering several factors (indication for LT, type of LT, presence of certain comorbidities, and microbiologic assessment before LT). A wider use of early nebulized therapies could be useful to prevent MDR colonization, thus potentially lowering infectious risk.

Revised Accelerated Moment Release Under Test: Fourteen Worldwide Real Case Studies in 2014–2018 and Simulations - Gianfranco Cianchini; Angelo De Santis; Rita Di Giovambattista; C. Abbattista; L. Amoruso; S. A. Campuzano; M. Carbone; C. Cesaroni; Anna De Santis; D. Marchetti; L. Perrone; A. Piscini; et al. (Pure and Applied Geophysics, 2020)

Interannual radial growth sensitivity to climatic variations and extreme events in mixed-species and pure forest stands of silver fir and European beech in the Italian Peninsula - S. Versace; D. Gianelle; V. Garfì; G. Battipaglia; F. Lombardi; M. Marchetti; R. Tognetti (European Journal of Forest Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Spatial diet overlap and food resource in two congeneric mullet species revealed by stable isotopes and stomach content analyses - A.F.S. Garcia; A.M. Garcia; S.R. Vollrath; F. Schneck; C.F.M. Silva; Í.J. Marchetti; J.P. Vieira (Community Ecology, 2018)

Peripheral and cerebrospinal fluid immune activation and inflammation in chronically HIV-infected patients before and after virally suppressive combination antiretroviral therapy (cART) - E. Merlini; F. Iannuzzi; A. Calcagno; F. Bai; M. Trunfio; A. d’Arminio Monforte; S. Bonora; Giulia Marchetti (Journal of NeuroVirology, 2018)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Toward an Improved Representation of Middle Atmospheric Dynamics Thanks to the ARISE Project - E. Blanc; L. Ceranna; A. Hauchecorne; A. Charlton-Perez; E. Marchetti; L. G. Evers; T. Kvaerna; J. Lastovicka; L. Eliasson; N. B. Crosby; P. Blanc-Benon; A. Le Pichon; et al. (Surveys in Geophysics, 2018)

Space-Wise approach for airborne gravity data modelling - D. Sampietro; M. Capponi; A. H. Mansi; A. Gatti; P. Marchetti; F. Sansò (Journal of Geodesy, 2017)

GTE: a new software for gravitational terrain effect computation: theory and performances - D. Sampietro; M. Capponi; D. Triglione; A. H. Mansi; P. Marchetti; F. Sansò (Pure and Applied Geophysics, 2016)

Streptococcus salivarius by nasal spray for recurrent otitis: how good is the evidence? - S. Di Mario; V. Basevi; R. D’Amico; C. Gagliotti; M. Gangemi; F. Marchetti; M. L. Moro; G. Tamburlini (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Implementing REDD+ in Papua New Guinea: Can biodiversity indicators be effectively integrated in PNG's National Forest Inventory? - G. Grussu; F. Attorre; D. Mollicone; P. Dargusch; A. Guillet; M. Marchetti (Plant Biosystems, 2014)

A CAD/CAM-prototyped anatomical condylar prosthesis connected to a custom-made bone plate to support a fibula free flap - L. Ciocca; S. Mazzoni; M. Fantini; F. Persiani; P. Baldissara; C. Marchetti; R. Scotti (Medical & Biological Engineering & Computing, 2012)

Comparison of forest stand structure and management of silver fir–European beech forests in the Central Apennines, Italy and in the Dinaric Mountains, Slovenia - F. Lombardi; M. Klopcic; P. Di Martino; R. Tognetti; G. Chirici; A. Boncina; M. Marchetti (Plant Biosystems, 2012)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

ForestBIOTA data on deadwood monitoring in Europe - D. Travaglini; A. Barbati; G. Chirici; F. Lombardi; M. Marchetti; P. Corona (Plant Biosystems, 2007)

Evaluation of Fungicidal Efficacy of Benzalkonium Chloride (Steramina G u.v.) and Virkon-S against Microsporum canis for Environmental Disinfection - V. Marchetti; F. Mancianti; G. Cardini; E. Luchetti (Veterinary Research Communications, 2006)

Microbial Reductive Dechlorination of Weathered and Exogenous Co-planar Polychlorinated Biphenyls (PCBs) in an Anaerobic Sediment of Venice Lagoon - G. Zanaroli; J. R. Pérez-Jiménez; L. Y. Young; L. Marchetti; F. Fava (Biodegradation, 2006)

Bacteriostatic and bactericidal activity of levofloxacin against clinical isolates from cystic fibrosis patients - G. Golini; F. Favari; F. Marchetti; R. Fontana (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Linear and non-linear analysis of surface electromyograms in weightlifters - F. Felici; A. Rosponi; P. Sbriccoli; G.C. Filligoi; L. Fattorini; M. Marchetti (European Journal of Applied Physiology, 2001)

Soybean Kunitz, C-II and PI-IV inhibitor genes confer different levels of insect resistance to tobacco and potato transgenic plants - S. Marchetti; M. Delledonne; C. Fogher; C. Chiabà; F. Chiesa; F. Savazzini; A. Giordano (Theoretical and Applied Genetics, 2000)

Biosynthesis and cytoplasmic accumulation of a chlorinated catechol pigment during 3-chlorobenzoate aerobic co-metabolism in Pseudomonas fluorescens - F. Fava; D. Di Gioia; C. Romagnoli; L. Marchetti; D. Mares (Archives of Microbiology, 1993)